EKSEKUSI HAK ATAS TANAH SEBAGAI OBYEK JAMINAN GADAI - Safriana, Rahmi (Program Pascasarjana Universitas Sunan Giri Surabaya, 2019)
The purpose of this research is to understand the implications of seized the execution of the sertificate rights to the land as collateral. Research with the approach of legislation and concept approach, obtained a conclusion as follows: Pledge guarantee is set in book II of civil Law about material that adheres to closed principle, which used as pawn object is moving goods whose supply is not by the Registration legal Act but rather the submission in real with the threat of insecurity if not done submission. A special land right to productive land that is still managed by natural resources, with the help of technology, capital, manpower, and management to produce agricultural commodities that includes food crops, horticulture, plantations, and/or farms in an agro-ecosystem, used as an object of collateral with the right of liability. The burden of liability is mandatory and with the registration of a submission of a sertificate rights that have the execution force as a court ruling which has a fixed legal force. Debtor if tort, on bail collateral will be difficult to execute a sertificate rights to the land due to the nature of mortgage submission of moving goods, in different with the rights of dependents, lenders can by self-rule do foreclosures and sale of the auction's rights